The influence of recycled aggregates from precast elements on the mechanical properties of structural self-compacting concrete. (10th September 2018) - Fiol, F.; Thomas, C.; Muñoz, C.; Ortega-López, V.; Manso, J.M.
Graphical abstract: Highlights: High-quality recycled aggregates (RA) produced from structural precast elements. Self-Compacting Concrete (SCC) manufactured with RA fulfilled current regulations. Slump loss due to water absorption of RA compensated with superplasticizers. SSC with different w/c ratios compared by extrapolation of fitted curves. Loss of stiffness is more limiting than loss of compressive strength. Abstract: Recycled Aggregates (RA) from structural precast elements and the performance of Self-Compacting Concrete (SCC) containing RA in percentage substitutions of 20%, 50% and 100% are described in this paper. Three Control Concretes (CC-30, CC-37.5, CC-45) manufactured with Natural Aggregates (NA), and their corresponding Recycled Aggregate Concretes (RAC-20, RAC-50, RAC-100) are evaluated in terms of physical and mechanical properties. The in-fresh properties results (flowability, viscosity and passing ability) of the RAC were suitable for their use as SSC. Furthermore, the tests of compressive, splitting tensile and flexural strength, as well as density, porosity, water absorption, ultrasonic pulse velocity, stiffness, and both dynamic and static modulus provided results close to those of the SCC with NA, and in compliance with the requirements of current regulations. The recycling process that takes place in the precast factory supposes an economical improvement and an important contribution to global sustainability, in accordance with the concept of the circular economy.